Single-site catalyst promoters accelerate metal-catalyzed nitroarene hydrogenation - Liang Wang (Nature Portfolio, 2018)
Understanding of the structures and roles of catalyst promoters markedly lags behind the understanding of the structures and roles of catalytic sites. Here, the authors address this challenge by incorporating a single-site promoter—tin—on a TiO2 surface to enhance the catalytic activity of various metals on the TiO2 in selective hydrogenation of nitroarenes.